Assortative Mating and Divorce: Evidence from Austrian Register Data - Wolfgang Frimmel; Martin Halla; Rudolf Winter-Ebmer (Verein für Socialpolitik, 2010)
This paper documents that changes in assortative mating patterns over the last four decades along the dimensions of age, ethnicity, religion and education are not responsible for the increasing marital instability. Quite the contrary, without the rise in the age at marriage, divorce rates would be considerably higher. Immigration and secularization, and the resulting supply of spouses with diverse ethnicity and religious denominations had no overall effect on divorce rates. Countervailing effects - in line with theoretical predictions - offset each other. The rise in the incidence in divorce is most probably caused by changing social norms.
Keywords: J12; J11; J15; 330; Assortative mating; divorce; marital instability; immigration